Spatial Heterojunction in Nanostructured TiO2 and Its Cascade Effect for Efficient Photocatalysis - Lu, Yi; Liu, Xiao-Long; He, Li; Zhang, Yue-Xing; Hu, Zhi-Yi; Tian, Ge; Cheng, Xiu; Wu, Si-Ming; Li, Yuan-Zhou; Yang, Xiao-Hang; Wang, Li-Ying; Liu, Jia-Wen; et al. (Nano Letters, 2020)
A highly efficient photoenergy conversion is strongly dependent on the cumulative cascade efficiency of the photogenerated carriers. Spatial heterojunctions are critical to directed charge transfer and, thus, attractive but still a challenge. Here, a spatially ternary titanium-defected TiO2@carbon quantum dots@reduced graphene oxide (denoted as VTi@CQDs@rGO) in one system is shown to demonstrate a cascade effect of charges and significant performances regarding the photocurrent, the apparent quantum yield, and photocatalysis such as H2 production from water splitting and CO2 reduction. A key aspect in the construction is the technologically irrational junction of Ti-vacancies and nanocarbons for the spatially inside-out heterojunction. The new "spatial heterojunctions" concept, characteristics, mechanism, and extension are proposed at an atomic-/nanoscale to clarify the generation of rational heterojunctions as well as the cascade electron transfer.
Created from Fastlane, Scopus look-up
Keywords: carbon dioxide reduction; cascade effect; seawater splitting; spatial heterojunction; Ti-vacancy